Fabrication of hierarchical porous cobalt manganese spinel graphene hybrid nanoplates for electrochemical supercapacitors. (10th January 2016) - Chen, Jun; Cui, Yanhui; Wang, Xiaoqing; Zhi, Mingjia; Lavorgna, Marino; Baker, Andrew P.; Wu, Junwei
Highlights: Mesoporous CoMn(CoMn)2 O4 /rGO composites were synthesized for electrochemical supercapacitors electrode. The composites with morphology of nanofibers or nanoplates were prepared by adjusting the solvent ratio. Nanopates have the highest capacity with the highest surface area and the smallest pore size. A large working potential window of 1 V and excellent cycling stability were presented in alkaline electrolyte. Abstract: Facile synthesis of porous and high conductive materials is highly desirable for supercapacitor electrode application. In this work, hierarchical porous CoMn(CoMn)2 O4 spinel coated on reduced graphene oxide (rGO) was synthesized successfully through mixed solvothermal process followed by calcination. By adjusting the solvent ratio of dimethyl formamide (DMF): deionized (DI) water used in the mixed solvothermal process, the surface morphology of CoMn(CoMn)2 O4 /rGO can be tuned from nanofiber to nanoplate. The nanoplates display the highest surface area of 133.1 m 2 g −1 with the pore size of ∼3 nm, whereas the corresponding electrode exhibits the highest capacitance of 571 F g −1 at a current density of 1 A g −1, with the working potential as high as 1 V. In addition, the electrode based on nanoplates can retain about 84% of the initial capacitance after 1500 cycles at a charge current density of 5 A g −1 . These results confirm that the mesoporous CoMn(CoMn)2 O4 nanoplates supported on rGO, synthesized the facile method described here, is a promising candidate for supercapacitor applications.